Exploring Mesozooplankton Insights by Assessing the Ecological Status of Black Sea Waters Under the Marine Strategy Framework Directive - Elena Bisinicu; Luminita Lazar (Oceans)
Mesozooplankton are highly responsive to environmental changes, making their population dynamics and species composition important indicators of large-scale oceanic conditions. This study investigates the mesozooplankton composition, emphasizing biomass values across all three marine reporting units in the Romanian Black Sea from 2013 to 2020, covering 45 stations that represent transitional, coastal, and marine waters during the warm season. It also examines environmental parameters, such as temperature, salinity, and nutrient levels associated with eutrophication, that impact the mesozooplankton, as well as the environmental status of the pelagic habitat in this region, influenced by various hydrological and anthropogenic factors. Statistical analyses, including multivariate methods, were employed to investigate correlations between mesozooplankton biomass and environmental parameters, facilitating ecological assessments in accordance with the Marine Strategy Framework Directive (MSFD) Descriptors 1 (Biodiversity) and 5 (Eutrophication) using indicators such as Mesozooplankton bBiomass, Copepoda Biomass, and Noctiluca scintillans iomass. The results indicated that Mesozooplankton and Copepoda Biomass did not reach good ecological status (GES). However, the Noctiluca scintillans Biomass indicator demonstrated that all marine reporting units achieved GES during the warm seasons. These findings underscore the dynamic nature of pelagic habitats and highlight the importance of ongoing monitoring to inform policy and conservation efforts.